2020
DOI: 10.1038/s41598-020-60442-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between MIR499A rs3746444 polymorphism and breast cancer susceptibility: a meta-analysis

Abstract: Numerous studies have investigated the association of MIR499A rs3746444 polymorphism with breast cancer susceptibility, but the results have been inconsistent. In this work, we performed a meta-analysis to obtain a more reliable estimate of the association between the polymorphism and susceptibility to breast cancer. A comprehensive literature search was conducted on PubMed, Scopus, Web of Science (WoS), China National Knowledge Infrastructure (CNKI), VIP and Wanfang databases up to January 2020. A total of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Allele C of rs11614913 in hsa-miR-196a-3p was found to be significantly associated with decreased risk of BC (C vs. T: OR = 0.64, 95%CI = 0.49-0.85, p = 0.0019) [42]. Allele G of rs3746444 in seed region of hsa-miR-499a-3p significantly increased BC susceptibility only among Asians (G vs. A: OR = 1.12, 95% CI = 1.00-1.26, P = 0.04) [43]. The G allele rs4919510 in hsa-miR-608 decreased the risk of BC (G vs. C: OR = 0.53, 95%CI 0.30-0.92, p = 0.024) [44].…”
Section: Discussionmentioning
confidence: 98%
“…Allele C of rs11614913 in hsa-miR-196a-3p was found to be significantly associated with decreased risk of BC (C vs. T: OR = 0.64, 95%CI = 0.49-0.85, p = 0.0019) [42]. Allele G of rs3746444 in seed region of hsa-miR-499a-3p significantly increased BC susceptibility only among Asians (G vs. A: OR = 1.12, 95% CI = 1.00-1.26, P = 0.04) [43]. The G allele rs4919510 in hsa-miR-608 decreased the risk of BC (G vs. C: OR = 0.53, 95%CI 0.30-0.92, p = 0.024) [44].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Rodriguez-Hernandez et al [ 41 ] showed that there was no significant association between the polymorphism and glioma risk. These inconsistencies could be due to numerous factors, such as the ethnicity of the study population, and the sample size (and thus statistical power) of the studies [ 70 , 71 ]. A well-conducted meta-analysis is essential to address these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis study showed that the MIR499A rs3746444 G allele is associated with high risk of developing breast cancer [ 52 ]. The allele G was also associated with hepatocellular carcinoma [ 53 ], and adenocarcinoma [ 54 ].…”
Section: Discussionmentioning
confidence: 99%